1995
DOI: 10.1016/0014-5793(95)00562-n
|View full text |Cite
|
Sign up to set email alerts
|

Composite control of cell function: metabolic pathways behaving as single control units

Abstract: This paper shows that under some conditions the control exerted by a part of a metabolic network (a pathway) on a flux or concentration in any other part can be described through a single (overall) control coefficient. This has the following implications: (i) the relative contributions of a pathway enzyme to the regulation of the pathway (output) flux and of any flux or concentration outside are identical; therefore, the control analysis of the pathway 'in isolation' allows one to determine the control exerted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Furthermore, mathematical models have so far only been applied to relatively small parts of plant metabolism (Gombert and Nielsen, 1999), and the paradigm of steady-state conditions that forms another basis of metabolic control analysis is also questionable (Giersch, 2000). In order to build models for large biochemical networks, some further simplifications have to be carried out, such as using matrix calculations of overall substrate-product stoichiometry (Kholodenko et al, 1995). Cornish-Bowden and Eisenthal (2000) emphasized the importance of the reliability of stoichiometric ratios when used for computer simulations and demonstrated that with such calculations, new links or non-obvious links in biochemical pathways could be found.…”
Section: Modelling Based On Biochemical Stoichiometrymentioning
confidence: 99%
“…Furthermore, mathematical models have so far only been applied to relatively small parts of plant metabolism (Gombert and Nielsen, 1999), and the paradigm of steady-state conditions that forms another basis of metabolic control analysis is also questionable (Giersch, 2000). In order to build models for large biochemical networks, some further simplifications have to be carried out, such as using matrix calculations of overall substrate-product stoichiometry (Kholodenko et al, 1995). Cornish-Bowden and Eisenthal (2000) emphasized the importance of the reliability of stoichiometric ratios when used for computer simulations and demonstrated that with such calculations, new links or non-obvious links in biochemical pathways could be found.…”
Section: Modelling Based On Biochemical Stoichiometrymentioning
confidence: 99%
“…Each of these motifs is then be replaced by supernodes that act similarly, in a way that is mathematically comprehensive. Hierarchical integration can lead to understanding of complex networks [17,23,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the identification of blocked reactions (i.e., reactions incapable of carrying flux due to the stoichiometry of the metabolic network under steady-state conditions) and enzyme subsets (i.e., groups of reactions that operate together in fixed flux proportions under steady-state conditions) in metabolic models has attracted considerable interest in recent years (Kholodenko et al 1995;Rohwer et al 1996;Pfeiffer et al 1999;. The output of these analyses provides significant biological insight as to which reactions are potentially missing from metabolic models, as well as which reactions may be under coordinated regulation, alluding to a mechanism for the continuous refinement of metabolic reconstructions through an iterative model-building process.…”
mentioning
confidence: 99%